Adoptability of Lean Construction Techniques in Pakistan’s Construction Industry - Aftab Hameed Memon; Muhammad Akram Akhund; Abdul Nasir Laghari; Hafiz Usama Imad; Shadab Noor Bhangwar (Civil Engineering Journal, 2018)
There is a philosophy in the construction industry to reduce the cost of a project by reducing construction waste and improving productivity. With lower expenses, lean construction emphasizes the cost of the project at a minimum cost. Globally, the philosophy has gained a wide range of popularity in the construction sector. The Lean Construction has helped practitioners with several tools and techniques to implement at different stages of a construction project. Following global trends, this study has investigated lean practices in Pakistan. With the potential advantages experienced by its implementation in Pakistan's construction projects and the level of implementation of various types of tools and techniques has been analyzed. To achieve the goal, the study had tried to capture construction projects in which four shareholders are being represented, which are clients, consultants, contractors and material suppliers. Overall 34 completed questionnaires were collected and then analyzed. The results of the analysis have indicated that pull approach, standard of work, time consuming, visualization tools, the integrated project delivery methods and the quality failure in safe limits are common lean techniques which are being implemented to the local construction industry. While there are major benefits of waste reduction, client satisfaction, better communication, visual control and proper task management to build appropriate work are the key benefits of lean construction.